Gas chromatographic determination of extracellular metabolites produced by baker's yeast during glucose-induced acidification - Wurst, M; Sigler, K; Knotková, A (Folia microbiologica, 1980)
Gas chromatographic separation of metabolites extruded during the medium acidification by resting baker's yeast supplied with glucose is described. Silylation with bis(trimethylsilyl)trifluoroacetamide and trimethylchlorosilane and a direct chromatography on Chromosorb G-AW-DMCS with 2.5% SE-52 (lactic, pyruvic, succinic, glyceric, fumaric, malic), polyols (glycerol, arabinitol) and sugars (glucose). The yeast was found to extrude glycerol, lactic, malic, and succinic acid.
Keywords: Chromatography, Gas; chromatografie plynová; Saccharomyces cerevisiae; Malates; glycerol; maláty; glukosa; laktáty; Glycerol; Lactates; Succinates; sukcináty; Glucose